'Safe Spaces': Experiences of Feminist Women-Only Space. (November 2015) - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of 'safe space' are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of 'safety' for women and, particularly, the meaning and experience of spaces they consider to be 'safe.' Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as 'safe space' to explore the significance and meaning of 'safety' in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being 'safe to' denotes fundamental aspects of civic engagement, personhood and freedom.